2015
DOI: 10.1007/s11999-014-3735-2
|View full text |Cite
|
Sign up to set email alerts
|

The John Charnley Award: Highly Crosslinked Polyethylene in Total Hip Arthroplasty Decreases Long-term Wear: A Double-blind Randomized Trial

Abstract: Background The use of highly crosslinked polyethylene (HXLPE) is now commonplace for total hip arthroplasty. Hip simulator studies and short-term in vivo measurements suggest that the wear rate of some types of HXLPE is significantly less than conventional ultrahigh-molecularweight polyethylene (UHMWPE). However, there are few long-term data to support its use. Questions/purposes The aim of this study was to measure the long-term steady-state wear of HXLPE compared with UHMWPE liners in a prospective, double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…Due to the low in vivo wear being reported for XLPE liners, it is important to understand the differences in the accuracy of the software programs currently used to measure wear. The reported accuracy for each method in the literature varies due to studies using different reference measurements, different directions of wear investigated, diverse statistical presentation of the error, and continuously updated versions of the software methods that incorporate different methods to identify the ellipse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the low in vivo wear being reported for XLPE liners, it is important to understand the differences in the accuracy of the software programs currently used to measure wear. The reported accuracy for each method in the literature varies due to studies using different reference measurements, different directions of wear investigated, diverse statistical presentation of the error, and continuously updated versions of the software methods that incorporate different methods to identify the ellipse.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of polyethylene wear of THA articulations involving highly cross‐linked polyethylene (XLPE) is significantly less than that of articulations with conventional ultra‐high molecular weight polyethylene (UHMWPE) . With wear rates below 0.1 mm/yr now commonly being reported, it is important to identify the accuracy of the methods used to measure such small movements.…”
mentioning
confidence: 99%
“…Due to differences in chemical affinities, elastic moduli, and hardness, Si 3 N 4 -on-XLPE bearings should not experience the same slip-stick behavior that was observed in the Si 3 N 4 -on-Si 3 N 4 couples, although additional simulator testing needs to confirm this supposition. Additionally, in vivo studies demonstrate excellent wear performance and survivability (currently >10 years) for ceramic-on-XLPE in comparison to ceramic-on-ceramic articulation [152][153][154][155]. Further XLPE improvements (e.g., vitamin E stabilization or phospholipid grafting) along with lower costs will build on these advances, favoring continued use and future growth of CoP bearings [47,[156][157][158].…”
Section: Swm Ceramic-on-ceramic Hip Simulator Studymentioning
confidence: 98%
“…The wear rates of metal‐on‐cross‐linked‐polyethylene (MoXLPE) bearing couples are typically less than 11 mm 3 /million cycles (Mc) compared with metal‐on‐non‐XLPE, which have reported wear rates ranging from 10 to 51 mm 3 /Mc . Clinical trials and mid‐ to long‐term follow‐up studies of XLPE have shown significantly reduced wear, less osteolysis, and a lower risk of revision than conventional non‐XLPE . A further point to note is that the revision rates for MoXLPE appear to vary according to the size of the femoral head, with 32‐mm femoral heads showing the lowest wear for MoXLPE in the AOANJRR…”
Section: Introductionmentioning
confidence: 99%